2015
DOI: 10.1534/genetics.115.181602
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide-Specific Targeting of the Tf1 Retrotransposon Promoted by the DNA-Binding Protein Sap1 of Schizosaccharomyces pombe

Abstract: Transposable elements (TEs) constitute a substantial fraction of the eukaryotic genome and, as a result, have a complex relationship with their host that is both adversarial and dependent. To minimize damage to cellular genes, TEs possess mechanisms that target integration to sequences of low importance. However, the retrotransposon Tf1 of Schizosaccharomyces pombe integrates with a surprising bias for promoter sequences of stress-response genes. The clustering of integration in specific promoters suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 60 publications
(95 reference statements)
3
40
0
Order By: Relevance
“…Genome-wide analysis showed that Sap1 binding is highly predictive of Tf1 insertion [36,56]. However, Sap1 binding is not sufficient for insertion, as some very strong Sap1 binding sites are cold spots for transposition.…”
Section: Role Of the Replication Fork In Transposon Target-site Sementioning
confidence: 99%
See 2 more Smart Citations
“…Genome-wide analysis showed that Sap1 binding is highly predictive of Tf1 insertion [36,56]. However, Sap1 binding is not sufficient for insertion, as some very strong Sap1 binding sites are cold spots for transposition.…”
Section: Role Of the Replication Fork In Transposon Target-site Sementioning
confidence: 99%
“…Additionally, Sap1 binding sites constitute insertion hotspots but only if they exhibit RFB activity, and their insertion competence depends on the orientation with respect to the advancing fork. However, other programmed RFB that are independent of Sap1 are not targeted for insertion [36,53,56]. These observations indicate that Sap1 binding and RFB activity are both necessary but neither is sufficient for target site selection.…”
Section: Role Of the Replication Fork In Transposon Target-site Sementioning
confidence: 99%
See 1 more Smart Citation
“…These LTR retrotransposons integrate at the transcription start site of Pol IIItranscribed genes and in subtelomeric regions, respectively (Kirchner et al, 1995;Xie et al, 2001). The Tf1 LTR retrotransposon of Schyzosaccharomyces pombe and the MLV retrovirus both target the promoter region of Pol II-transcribed genes (Gupta et al, 2013;Hickey et al, 2015;Jacobs et al, 2015;De Rijck et al, 2013;Sharma et al, 2013), and the HIV-1 retrovirus targets the gene body of Pol II-transcribed genes (Cherepanov et al, 2003;Llano et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In S. pombe, Tf1 preferentially integrates into nucleosome-free promoters of Pol II-transcribed genes with an enrichment of stress-responsive genes (Chatterjee et al, 2014;Guo & Levin, 2010). The DNA-binding factor Sap1 and its replication fork barrier activity collaborate to determine Tf1 target site selection (Hickey et al, 2015;Jacobs et al, 2015). In S. cerevisiae, Ty5 integrates into nucleosome-free regions at subtelomeres and silent mating-type loci (HM) through an interaction between its integrase and the Sir4 heterochromatin protein (Baller et al, 2011;Xie et al, 2001).…”
Section: Introductionmentioning
confidence: 99%